PENGARUH TATA KELOLA PERUSAHAAN DAN PENGGUNAAN DERIVATIF KEUANGAN TERHADAP EFFECETIVE TAX RATE (ETR) PERUSAHAAN - Gilang Raka Sista; Moh Didik Ardiyanto (Diponegoro Journal of Accounting, 2017)
The purpose of this study is to examine the influence of corporate governance and the use of financial derivatives effective tax rate (ETR) company with company size and ROA as control variables. This study used secondary data. The population in this study consisted of all manufacturing companies listed in Indonesia Stock Exchange in 2013 - 2015. The sampling method in this research is purposive sampling, and obtained a total sample of 54 companies. This study used the technique of multiple linear regression analysis. The empirical results of this study show that Compensation management has a negative influence and significant impact on the effective tax rate (ETR). While Background accounting expertise or finances of the audit committee, structure of the largest shareholders and Use of financial derivatives have no influence on effective tax rate (ETR).